Caffeine Prolongs Survivability And Significantly Modulates Cytokine Levels of TNF-a, IFN-, IL-18 and IL-10 in Plasmodium berghei ANKA-infected ICR Mice (Early view) - Ahmad Zakwan Noriman, Mohd Ridzuan Mohd Abd Razak, Wan Nurhayati Wan Hanafi, Rusliza Basir, Hani Kartini Agustar; Wan Rozianoor Mohd Hassan (Tropical Life Sciences Research, 2026)
Caffeine, a bioactive compound in Theobroma cacao, exhibits various pharmacological activities, including anti-inflammatory property. Malaria is an inflammatory-related disease caused by Plasmodium spp. Severe infection of this disease can cause cerebral malaria, which is characterized by neuroinflammation. An in vitro study of caffeine suggested that it possesses anti-malarial property. However, caffeine’s potential in both anti-malarial and cytokine-modulating properties through in vivo have yet to be explored. This study investigated anti-malarial and cytokine-modulating effects of caffeine in P. berghei ANKA-infected ICR mice. Anti-malarial activity of caffeine at 5, 10, and 20 mg/kg body weight were given via intraperitoneal (i.p.) injection and the chemosuppressive percentage (percentage of parasitemia inhibition) was calculated based on Peter and Robinsons (1992). In addition, the cytokine-modulating effect was determined using the ELISA method. Chemosuppressive test at 5, 10 and 20 mg/kg b.w. of caffeine in the P. berghei ANKA-infected ICR mice exhibited 64.18 ± 9.17, 39.93 ± 5.63, and 21.86 ± 5.57%, respectively. Notably, the lowest concentration, 5 mg/kg b.w. of caffeine was able to prolong significantly (p < 0.05) the survivability of malaria-infected ICR mice for 17 days as compared to infected mice (12 days). This effective dose of caffeine revealed a significant reduction in cytokine levels of TNF- α, IFN- g, IL-18, and IL-10 by 1.08-, 1.12-, 1.12-, and 1.15-folds as compared to malaria-infected mice. Collectively, 5 mg/kg b.w. of caffeine exhibited good chemosuppressive, modulated levels of inflammatory cytokines and prolonged survivability of P. berghei ANKA-infected ICR mice. Hence, caffeine can be a plausible candidate for the development of anti-malarial therapeutic drugs.